Transparency and Disclosure in the Implementation of Fintech and AI by Financial Service Institutions in Sustainability Reports - Wiwiek Prihandini; Wiwiek Prihandini (Journal of Central Banking Law and Institutions, 2026)
This study evaluates the application of financial technology (FinTech) and artificial intelligence (AI), as well as the transparency of their disclosure in Sustainability Reports across four types of financial service institutions (FSIs) in Indonesia: banks, insurance companies, finance companies, and securities firms. By analysing the content of 20 Sustainability Reports, this study finds that banks have the highest level of technology implementation and disclosure, followed by finance, insurance, and securities firms. Although FinTech and AI contribute to operational efficiency, service innovation, and the expansion of financial access, disclosures related to these technologies are still limited in Sustainability Reports, often using terms like “digitalisation” without explicit explanation. These findings underscore the importance of enhanced transparency in technology disclosure to foster public trust and accountability, as well as to ensure compliance with regulations such as the OJK Regulation on Sustainable Finance. This study recommends strengthening reporting standards and regulatory guidelines to improve technology disclosures in the financial sector, thus enabling a sustainable andinclusive digital financial ecosystem.